Strength of Materials: Construction Diagrams of Internal Forces : Methodical recommendations, tasks and examples - Kosshevyi, Oleksandr Oleksandrovych; Yansons, Maryna Oskarivna (KNUCA, 2026)
The methodological guidelines contain variants of individual assignments and detailed plans for performing calculation and graphic works for the course "Strength of Materials", as well as solution examples for each task. The section "Construction of Internal Force Diagrams" is covered. For students pursuing the first (Bachelor’s) level of higher education, in specialties G19 Building and Civil Engineering. Educational programs: Heat and Gas Supply and Ventilation (HGSV); Water Supply and Wastewater Disposal (WSWD). Містять варіанти індивідуальних завдань та детальні плани виконання розрахункових і графічних робіт з курсу «Опір матеріалів», а також приклади розв’язання кожного завдання. Розглянуто розділ «Побудова епюр внутрішніх зусиль». Призначено для здобувачів першого (Бакалаврського) рівня вищої освіти за програмою G19 «Будівництво та цивільна інженерія», що навчаються англійською мовою. Освітні програми: «Теплогазопостачання і вентиляція» (ТГВ); «Водопостачання та водовідведення» (ВВ).
Опір матеріалів: Побудова епюр внутрішніх зусиль : методичні вказівки, завдання та приклади
Keywords: 539.3